Better Than Most : Teacher Beliefs about Effort and Ability in Uganda - Sabarwal, Shwetlena; Kacker, Kanishka; Habyarimana, James (World Bank, Washington, DC, 2018)
Do teachers have accurate beliefs about their effort and ability? This paper explores this through a survey experiment in public-private partnership schools in Uganda, wherein teacher self-beliefs are contrasted with their beliefs about other teachers in the same school. The study finds that, on average, teachers tend to rate ability, effort, and job satisfaction more positively for themselves than for other teachers. This tendency is called high relative self-regard. The study finds no systematic evidence of high relative self-regard around perceptions of student engagement quality and available support structures. More experienced teachers are less likely to exhibit high relative self-regard, while teachers showing low effort are more likely to exhibit it. This is analogous to the Dunning-Kruger effect in psychology, except respondents rate themselves as better than most (not better than average) and variation is explored over effort (not cognitive ability). High relative self-regard is less pronounced in owner-managed public-private partnership schools, suggesting that when principle-agent problems are less severe, schools find ways to correct for inaccurate teacher self-beliefs. These results provide suggestive evidence of cognitive biases that help teachers rationalize suboptimal effort in the classroom. This in turn points to the importance of providing objective feedback to teachers about their effort and performance as one potential way to improve their performance. Teacher self-beliefs are important areas of intervention because they are likely to affect how teachers optimize their effort and training investments. Self-beliefs are also likely to affect how teachers respond to changes in incentive and accountability regimes.